Professionalism in nursing in Ethiopia: systematic review and meta-analysis - Edmealem, Afework; Ayenew, Temesgen; Ayenew, Setarg; Tegegne, Belachew; Ademe, Sewunet; Esubalew, Dereje; Getie, Addisu; Liknaw, Tiliksew (Frontiers in Medicine, 2025)
BackgroundIn any field, professionalism is essential. A profession can fulfill its responsibilities when professionals develop their knowledge in various ways, such as continuing professional development, expanding their skill levels, adhering to the norms of the profession, and demonstrating high levels of commitment. Developing professionalism in nurses is a key strategy for improving the quality of nursing care and healthcare. However, no study has shown a comprehensive overview of professionalism in nursing in Ethiopia. Thus, this systematic review and meta-analysis aim to present a comprehensive assessment of the overall level of professionalism in nursing in Ethiopia.MethodsThe Preferred Reporting Items for Systematic Review and Meta-Analysis standard was followed in the reporting of this systematic review and meta-analysis. An extensive exploration of digital repositories, including PubMed (MEDLINE), EMBASE, Cochrane, Africa Journal of Online, Google Scholar, and an advanced Google search, was conducted to obtain published studies detailing professionalism in nursing in Ethiopia. STATA version 17 commands created the pooled estimate with a 95% confidence interval. The I2 test and Egger’s test were used to identify the presence of heterogeneity and publication bias, respectively. To manage heterogeneity, a subgroup analysis and random effect model were used.ResultsA total of 11 articles with a total of 3,581 participants were included in the final systematic review and meta-analysis. The pooled estimate of professionalism in nursing in Ethiopia was 54% (95% CI: 44, 66%). In the subgroup analysis, the highest pooled estimate of professionalism in nursing was observed in South Ethiopia, which is 64% (95% CI: 43–86%).ConclusionThe level of professionalism in nursing in Ethiopia is suboptimal. Being female, having a higher educational level, having long years of experience, having a low workload, having favorable job satisfaction, being a member of a nursing organization, having a good working environment, working in non-stressful units, and having a good organizational culture were the major factors that had a positive association with professionalism in nursing. Therefore, healthcare professionals, the Ministry of Health, and other stakeholders should focus on interventions to enhance the organizational culture, job satisfaction, working unit, and working schedule for nurses.